Supernatant of plant-associated bacteria potency against biofilms formed by foodborne pathogen and food spoilage bacteria - Gabriella Gandasurya; Diana Elizabeth Waturangi; Nurmaya Papuangan; Nurhasanah; Pande Gde Sasmita Julyantoro (BMC Research Notes)
Abstract Objectives Food products are often contaminated by pathogens and spoilage bacteria. Most of them can form biofilms, a community of cells embedded in protective extracellular matrix layers resistant to harsh conditions, including antibiotics. Therefore, alternative antibiofilm agents are required to overcome biofilm formation. This study aims to determine and quantify the antibiofilm activity of supernatants from plant-associated bacteria against biofilms of foodborne pathogen and food spoilage bacterium, namely Bacillus cereus and Bacillus subtilis. Results Plant-associated bacteria (PAB) have shown promising antibiofilm activities against biofilm-forming pathogens in previous studies. Thirteen PAB isolated from Ternate, Indonesia were used in this study. Supernatants of PAB were subjected to antimicrobial activity and quorum quenching detection, both using the well diffusion method. Four supernatants inhibited the growth of B. subtilis, but none affected the growth of B. cereus. Eight supernatants were able to disrupt the quorum sensing system of an indicator bacterium, wild-type Chromobacterium violaceum. Biofilm inhibition and destruction were quantified using 96-well microplates. The highest biofilm inhibition and destruction activities of PAB supernatants against each of B. cereus and B. subtilis biofilms were > 76%, and were later confirmed by light microscope and scanning electron microscope. Brine shrimp lethality assay (BSLA) was conducted and revealed that the selected PAB supernatants were non-toxic. The 16S rRNA gene of PAB were sequenced and they showed similarities to Bacillus, Priestia, and Chryseobacterium. Compounds in the supernatants were determined by GC–MS which revealed contents of fatty acids, ethyl esters, and diketopiperazines. Therefore, PAB supernatants have potential as antibiofilm agents against biofilm formed by Bacillus cereus and Bacillus subtilis.